Post-transcriptional regulation of metallothionein isoform 1 and 2 expression in the human breast and the MCF-10A cell line - Gurel, Volkan; Sens, Donald A; Somji, Seema; Garrett, Scott H; Weiland, Tim; Sens, Mary Ann (Toxicological sciences, 2005)
Studies have shown, using immunohistochemical staining, that the MT-1 and MT-2 proteins (MT-1/2) are overexpressed in a substantial subset of ductal breast cancers, that overexpression occurs early in the disease process, and that this overexpression is indicative of a poor prognosis. Normal ductal breast epithelium fails to immunostain for the MT-1/2 protein, whereas the myoepithelial cells of the ducts stain intensely. There is no information regarding the expression of the mRNAs for the eight active MT-1 and MT-2 genes in normal breast duct epithelium. Microdissection of normal breast samples was used to obtain total RNA from enriched populations of ductal epithelium and myoepithelium. Analysis by reverse-transcription polymerase chain reaction (RT-PCR) demonstrated that the identity of the MT isoform-specific genes expressed (MT-2A and MT-1X) and their relative levels of expression were similar between the myoepithelial and ductal components. These findings indicate that the ductal and myoepithelial components express similar amounts of MT-2A and MT-1X mRNAs, but that they have distinctly different expression of the MT-1/2 protein. Confluent cultures of MCF-10A breast epithelial cells were exposed to Cd(+2) to test for evidence of post-transcriptional regulation of MT-1/2 protein accumulation in ductal epithelium. It was demonstrated that Cd(+2) elicited only a marginal induction of MT-1E, MT-1X, or MT-2A mRNAs, whereas, there was a marked increase in MT-1/2 protein, reaching levels of 6% of total cell protein under conditions of extended exposure. This study suggests that the mechanism underlying the finding of increased MT-1/2 protein expression in ductal breast cancer may involve, to some degree, the post-transcriptional regulation of MT-1/2 protein expression.